2020
DOI: 10.3390/ijms21144909
|View full text |Cite
|
Sign up to set email alerts
|

Viburnum opulus L. Juice Phenolic Compounds Influence Osteogenic Differentiation in Human Osteosarcoma Saos-2 Cells

Abstract: Bone mass loss occurs with a decrease in osteoblast proliferation and differentiation, or the enhancement of bone resorption, which further leads to the impairment of bone mineral density and increase in bone fracture. Recent studies suggest that some phenolic compounds found in food play positive role in bone metabolism. High content of phenolic compounds with potential beneficial effects on bone metabolism have been identified in the Viburnum opulus fruit. The aim of the study was to determine the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…This effect results from the efficient removal of non-phenolic compounds, such as organic acids, proteins, or unbounded sugars. More potent activity of the isolated phenolic compounds is in accordance with previously published data [37,[41][42][43][44]. Still, our studies confirmed that M. chamomilla phenolic compounds potentially decreased the NBDF uptake by downregulation of GLUT5 level [22,33].…”
Section: Discussionsupporting
confidence: 92%
“…This effect results from the efficient removal of non-phenolic compounds, such as organic acids, proteins, or unbounded sugars. More potent activity of the isolated phenolic compounds is in accordance with previously published data [37,[41][42][43][44]. Still, our studies confirmed that M. chamomilla phenolic compounds potentially decreased the NBDF uptake by downregulation of GLUT5 level [22,33].…”
Section: Discussionsupporting
confidence: 92%
“…Magnesium is also important for bone health. Interestingly, SaOS-2 cells display osteoblastic features similar to primary human osteoblastic cells and are often used as a model of osteogenic differentiation [ 20 , 46 ]. A recent review showed how optimal magnesium and vitamin D balance may improve bone metabolism and health outcomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of both factors, IL-6 and TNF-α, have been diagnosed in people with obesity and osteopenia [ 62 ]. The reduction of the secretion of IL-6 and TNF-α by V. opulus juice was observed in Saos-2 cells, therefore showing that the juice may be important not only for the metabolism of bone tissue but also may delay its demineralization resulting from obesity [ 63 ]. Despite the observed positive, or at least neutral, effects of the digestion process on V. opulus fruit juice’s biological activity, there was one negative aspect determined.…”
Section: Discussionmentioning
confidence: 99%